Espacios de unidad entre humanos - Aragón Quintero, José Ariel (Universidad Pedagógica y Tecnológica de Colombia, 2019)
According to decree 4500 of 2006 about the right to religious freedom, the possibili- ty of harmony between the different truths of a whole is welcomed to understand in detail our human nature and enter in the hope of a perfect social coexistence Which must be manifested in the effort for a greater understanding of the other in their particular circumstances, which in dialogue with other forms of word and knowledge based on the enigmatic space of the ‘inner life’ indicate a principle Integral to the liberating and transforming knowledge and at the same time, a hope, which under the theological name of ‘God of God’ define an ideal way for us and our specific situation - at the local and national ambit - as a spiritual offering of great tradition And reach to be used pedagogically today.